Crestal bone loss around dental implants placed in head and neck cancer patients treated with different radiotherapy techniques: a prospective cohort study. Issue 5 (May 2019) - Papi, P.; Brauner, E.; Di Carlo, S.; Musio, D.; Tombolini, M.; De Angelis, F.; Valentini, V.; Tombolini, V.; Polimeni, A.; Pompa, G.
Abstract: The aim of this prospective cohort study was to evaluate how the radiation technique can affect crestal bone loss and the implant survival rate in head and neck cancer patients treated with radiotherapy. In this study, the type of radiotherapy treatment, i.e. three-dimensional conformal radiotherapy (3D-CRT) or intensity modulated radiation therapy (IMRT), was the predictor variable. The primary outcome variable was crestal bone loss, recorded at implant placement and after 3, 6, 12, and 24 months. A descriptive analysis and ANOVA test were performed; significance was set at P < 0.05. Thirty-two patients were enrolled and a total of 113 dental implants placed in irradiated residual bone. There was no statistically significant difference in crestal bone loss levels between the groups at any of the intervals ( P > 0.05), except after 6 months ( P = 0.028). The cumulative dental implant survival rate was 94.7%. After 24 months, the mean marginal bone loss was 0.83 ± 0.12 mm in the 3D-CRT group and 0.74 ± 0.15 mm in the IMRT group ( P = 0.179). The data suggest that the different radiation techniques did not affect the outcomes of implant-supported prosthetic rehabilitation, as related to crestal bone loss and implant survival. However, long-term follow-up studies are necessary to evaluate the real influence of the radiotherapy technique on dental implants.